Testing for Seasonal Integration and Cointegration: An Expository Note with Empirical Application to KLSE Stock Price Data - Habibullah, Muzafar Shah (Universiti Putra Malaysia Press, 1998)
The purpose of this paper is to investigate the seasonal properties of the sectoral stock price series at the Kuala Lumpur Stock Exchange (KLSE) for the period 1978:1 to 1992:3. Our results suggest that the stock price indices at the KLSE exhibit seasonal unit roots, not only at the zero frequency, but in most cases at the biannual frequency. The finding that stock price indices exhibit seasonal integration has important implications for seasonal cointegration. However, our seasonal cointegration test results suggest that sectoral stock price indices at the KLSE are not seasonally cointegrated. These results imply that the informationally efficient stock market hypothesis cannot be rejected for the KLSE.